Greetings and interpersonal closeness: The case of Bengalis on Orkut. (March 2016) - Das, Anupam; Herring, Susan C.
Abstract: This study investigates to what extent greetings on a social network site popular with South Asians are associated with the degree of interpersonal closeness of the users, educated middle class Bengalis in the United States. Computer-mediated discourse analysis, face-to-face interviews, and participant observation were employed to analyze the textual comments exchanged in 79 Bengali dyads. The analyses reveal a relationship between degree of social distance and frequencies of Bangla greetings when type of greeting (regular vs. ritualistic) and manner of expression (unmarked vs. intensified) are taken into account. However, some aspects of the interplay between interpersonal closeness and greetings can only be understood if cultural nuances and medium factors are taken into consideration. Highlights: Types and manner of expression of Bangla greetings are associated with social distance. Intensified and unmarked greetings index degree of interpersonal closeness, but in opposite directions. These findings resemble the left half ofWolfson's (1988, 1989) politeness 'bulge'. No significant association was found between ritualistic greetings and interpersonal closeness. Cultural and medium factors influence the use of ritualistic greetings.